Imperialismo e estratégia revolucionária - Rocha, Cindy Gonçalves (2018)
This dissertation, which has bibliographic character and is a theoretical investigation, is based on the Marxian ontology, seized and systematized by Karl Marx (1818-1883) through the method of dialectical and historical materialism, and is also based in political-philosophical categories elaborated from this matrix. The new general inclinations of the world economy's movement, notorious in the West since the so-called "brief twentieth century", in which the constant revolution of the means of production, reaching certain levels, releases forces so powerful that turns into a contradiction with the very same social relations which engenders them, becoming an obstacle that calls into question the continuity of capitalism. The capitalism by its turn, through modulations of the being to the non-being, manages to restructure itself, elevating itself to a superior phase, not without becoming its antithesis, alternating from free competition to the pattern of monopolistic relationship. This dissertation is also based on the contributions of Vladimir Lenin (1870-1924), which provides a concrete and assertive picture of the new and complex plot inaugurated with imperialism, involving the whole globe. Circumscribed in that context are important historical experiences of the working class in confrontation and opposition to capitalism, among which one focus on the analysis of both the Russian Revolution (1917) and Cuban Revolution (1959). From the innumerable anxieties and problems aired with the hegemony of financial capital, one aim to analyze new determinations that affect the dynamics of the classes and pose as challenges to the continuity of the anti-imperialist struggle.